2018
DOI: 10.13075/ijomeh.1896.01169
|View full text |Cite
|
Sign up to set email alerts
|

Presence and use of automated external defibrillators in occupational setting, Belgium

Abstract: Acquiring an AED in the occupational setting is seldom based on a well-conducted risk analysis. Therefore, instructions and criteria are needed to come to a rational decision. Furthermore, a registry on AED utilization in the workplace (e.g., with data on long-term survival) should be set up. Int J Occup Med Environ Health 2018;31(5):603-611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Approximately 49% of companies who took part in a questionnaire-based survey in Belgium in 2012 and 2014 had an AED on their premises. 61 Outcome after out-of-hospital cardiac arrest have highlighted the importance of each country knowing its outcomes from OHCA and striving to improve them. 62 The EuReCa TWO study reported an overall survival rate of 8% after OHCA in Europe.…”
Section: Chain Of Survivalmentioning
confidence: 99%
“…Approximately 49% of companies who took part in a questionnaire-based survey in Belgium in 2012 and 2014 had an AED on their premises. 61 Outcome after out-of-hospital cardiac arrest have highlighted the importance of each country knowing its outcomes from OHCA and striving to improve them. 62 The EuReCa TWO study reported an overall survival rate of 8% after OHCA in Europe.…”
Section: Chain Of Survivalmentioning
confidence: 99%
“…However, due to the cost of AEDs, it is only possible to place a limited number of them; therefore, their location must be methodical to ensure that they are as effective as possible. In addition to public AEDs, some AEDs are privately owned (by private communities or enterprises) and are placed based on different criteria (e.g., number of visitors, specific risks, marketing, to improve the company’s image), rather than following a well-conducted risk analysis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%